Опыт русского романа второй половины XIX – первой половины XX в. и исторический роман Теодора Парницкого Сeребряные орлы - Oleander, Luiza (Acta Polono-Ruthenica, 2008)
This article is about the discoveries in renewal of the novel’s form by L. Leonov and T. Parnytsky, their typological community is defined, innovation of Polish writer is characterized.